2017
DOI: 10.1016/j.amepre.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Interventions Targeting Obesity: Research Recommendations for Vulnerable Populations

Abstract: Introduction The origins of obesity are complex and multifaceted. To be successful, an intervention aiming to prevent or treat obesity may need to address multiple layers of biological, social, and environmental influences. Methods NIH recognizes the importance of identifying effective strategies to combat obesity, particularly in high-risk and disadvantaged populations with heightened susceptibility to obesity and subsequent metabolic sequelae. To move this work forward, the National Heart, Lung, and Blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 95 publications
0
44
0
Order By: Relevance
“…Another focus of interest remains in the ability to identify subjects at risk of gaining weight over time. More vulnerable population segments comprise children, low-income individuals, racial/ethnic minority groups, low educational level, rural populations, and adults aged >65 years (31,32). In our 10year paired cohort study, we have shown that preventive healthy public strategies must be focused and intensified in younger women with lower BMI.…”
Section: -2008mentioning
confidence: 80%
“…Another focus of interest remains in the ability to identify subjects at risk of gaining weight over time. More vulnerable population segments comprise children, low-income individuals, racial/ethnic minority groups, low educational level, rural populations, and adults aged >65 years (31,32). In our 10year paired cohort study, we have shown that preventive healthy public strategies must be focused and intensified in younger women with lower BMI.…”
Section: -2008mentioning
confidence: 80%
“…This is particularly important as obesity is increasingly recognized as a chronic health condition and a growing public health problem worldwide. Interdisciplinary, multicomponent interventions are needed at the individual, community, and policy levels (10). We hope that this Research Topic will stimulate further work in this important area.…”
Section: Psychosomatic Aspects Of Obesitymentioning
confidence: 98%
“…As such, it is of vital importance for interventions to be developed with a focus on implementation, and the multiple levels of behaviours required to facilitate implementation and intervention delivery, from the outset (Brownson et al , ; Chambers & Norton, ; Pluye, Potvin, & Denis, ; Schell et al , ). Incorporating insights from a variety of stakeholders including practice, policy, and patient/public enables several levels of behavioural factors influencing implementation to be considered, and has been consistently acknowledged as one of the most important aspects in developing sustainable public health interventions (Iwelunmor et al , ; Proctor et al , ; Schell et al , ; Stevens et al , ). However, incorporating multiple stakeholder perspectives within intervention development is not straightforward (Cottrell et al , ; Deverka et al , ).…”
Section: Introductionmentioning
confidence: 99%